Frequency and Pattern of Presentation of Mental Nerve Injury During Para Symphysis Fracture - Ahsan Iqbal, Asif Nazir, Tania Rashid, Saima Sultan, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The mandibular fracture at the parasymphysis is the most often seen fracture of a facial bone. The occurrence of anaesthesia or paraesthesia in the skin and mucous membrane within the distribution of the mental nerve may be seen due to mental nerve injury resulting from fractures in the Parasymphysis region. This condition has the potential to impact the overall well-being of affected individuals. Objective: To determine the Frequency and pattern of presentation of mental nerve injury during Para symphysis fracture. Method: The present research is an observational and descriptive investigation including a sample of 65 patients diagnosed with parasymphysis fracture. The study was done at the Nishter Institute of Dentistry in Multan, Pakistan, spanning from September 2021 to February 2023.Following the endorsement of the research by the Ethical Review Board of the hospital, patients were recruited using a non-probability sequential sampling method. The researchers used clinical neuro-sensory testing (NST) as a means of evaluating nerve damage and determining the specific kind of neurosensory impairment that occurred subsequent to a para symphysis fracture. A specifically prepared proforma is used as a tool for data collecting. The data underwent statistical analysis, and findings and observations were derived from the analysis. Results: The study assessed the incidence of mental nerve damage in instances with Para symphysis fracture, revealing that 23 cases (35%) exhibited the presence of mental nerve injury, whereas it was missing in 42 cases (65%). The study observed a total of 23 individuals, consisting of 17 males and 6 females, who were diagnosed with mental nerve damage. The most often encountered neurosensory problems experienced by patients after surgery are paraesthesia. Additionally, it has been shown that the leading cause of parasymphysis fracture in both males and females is road traffic accidents (RTA). Conclusions: Road traffic accidents (RTAs) have been identified as a significant factor contributing to parasymphysis fractures. These fractures may result in the development of neurosensory deficits either as a consequence of the initial trauma or as a complication after surgical intervention. It has been seen that such fractures can lead to persistent complications and a decrease in overall quality of life. Additionally, it is essential to conduct additional research studies that cover a longer duration and include a bigger cohort of patients. Keywords: Mandibular fracture, Mental nerve, Paraesthesia, Trauma